KORELASI PERSEPSI DOSEN TERHADAP KEMAMPUAN MANEGERIAL DEKAN DENGAN MOTIVASI BERPRESTASI DOSEN DI LINGKUNGAN UNIVERSITAS BATANGHARI - Jonner Simarmata (Universitas Batanghari Jambi, 2017)
It is believed that managerial skills of a leader significantly affect the motivation of employees. This research aims at finding whether or not deans’ managerial skills of Pedagogics Faculty (X1), Economics Faculty (X2), Law Faculty (X3), Engeneering Faculty (X4) and Agriculture Faculty (X5) of Batanghari University significantly affect achievement motivation of leacturers of Pedagogics Faculty (Y1), Economics Faculty (Y2), Law Faculty (Y3), Engeneering Faculty (Y4) and Agriculture Faculty (Y5) of Batanghari University respectively. For this purpose, questionnaire was distributed to 77 respondents who were randomly selected from the five faculties to obtain data. Then, the data collected was analyzed by using simple correlation analysis of Pearson Product Moment and simple regression analysis. The t-test at the level of 95% was used to test the hypotheses. The result of the analysis shows that 1) X1 is proved not to correlate significantly with Y1. This means that dean’s managerial skills have no affect on lecturers’ achievement motivation in Pedagogics Faculty with contribution of only 5%. This also means that dean’s managerials skills cannot be used to improve lecturers’ achievement motivation in Pedagogics Faculty, 2) X2 is proved not to significantly correlate with Y2. This means that dean’s managerial skills have no affect on lecturers’ achievement motivation in Economics Faculty with contribution of only 14%. This also means that dean’s managerial skills cannot be used to improve lecturers’ achievement motivation in Economics Faculty, 3) X3 is proved no to significantly correlate with Y3. This means that dean’s managerial skills have no affect on lecturers’ achievement motivation in Law Faculty with contribution of only 19%, This also means that dean’s managerial skills cannot be used to improve lecturers’ achievement motivation in Law Faculty, 4) X4 is proved not to significantly correlate with Y4. This means that dean’s managerial skills have no affect on lecturers’ achievement motivation in Engenerring Faculty with contribution of only 1%. This also means that dean’s managerial skills cannot be used to improve lecturers’ achievement motivation in Engeeering Faculty, 5) X5 is proved to correlate significantly with Y5. This means that dean’s managerial skills have significant affect on lecturers’ achievement motivation in Agriculture Faculty with contribution of 56%. This also means that dean’s managerials skills can be used to improve lecturers’ achievement motivation in Agriculture Faculty. Regression analysis shows that Y5 = 0.48 + 0.35(X5). Ini berarti if dean’s managerial skills of Agricultural Faculty (X5) increases by 1 then lecturers’ achievement motivation of Agriculture Faculty (Y5) will increase by 0.39.Key Words: dean’s managerial skills, lecturer’s achievement motivation